Multicarrier CDMA for cellular overlay systems. - Rainbolt, B.J (IEEE Journal on selected areas in communications)
A code-division multiple access (CDMA) cellular overlay system is investigated, employing the idea of multicarrier CDMA, which has previously received significant attention as an alternative to traditional single-carrier CDMA. Overlay is pursued here as a means of long-term transition from narrowband cellular to CDMA cellular. A major result of this paper is the demonstration that the use of multicarrier CDMA in a fading channel is particularly beneficial to the narrowband system, as the CDMA users can reduce their transmitted powers as a result of diversity. Another significant conclusion is that the use of transmitter notching in the CDMA system in order to avoid active narrowband users outperforms a strategy in which a narrowband user is avoided by simply dropping the particular carrier which overlays it. Finally, results on the use of the minimum mean-squared error (MMSE) receiver in a fading channel are extended for use in the overlay scenario